Evaluating the Argument Quality of Students' Argumentative Podcasts Using the Toulmin Argument Model - Elma Indriyani; Issy Yuliasri (Journal of English Language Learning, 2026)
This study examines the quality of students’ arguments in argumentative podcasts by applying the Toulmin Argument Model. Although previous research has largely focused on written works such as essays, this study fills a research gap by providing empirical evidence on how arguments are constructed through video podcasts in English as a Foreign Language (EFL) classrooms. Using a qualitative descriptive research design, the researcher analyzed 28 argumentative podcasts produced by 12th-grade students at a state high school in Semarang. The analysis categorized the arguments into four levels of quality: Incomplete, Semi-Complete, Almost-Complete, and Complete. The results indicate that the incomplete pattern (consisting only of a claim and supporting data) was the most frequent, appearing in 10 units of podcasts (36%). The nearly complete pattern was found in 7 units (25%), the semi-complete pattern with 6 units (21%), and the complete pattern was found in 5 units (18%). These findings indicate varying levels of ability among high school students in presenting structured arguments in digital formats. This highlights the need for sustained guidance to maximize the use of podcasts in constructing comprehensive arguments in digital media.